Special Issue Editorial: “Remote Sensing in Structural Health Monitoring” - Yang Yang; Giuseppe Lacidogna; Mohamed Elchalakani; Craig M. Hancock (Remote Sensing)
Structural Health Monitoring (SHM) plays an indispensable role in ensuring the safety and longevity of critical infrastructure, including bridges [...]